A study of activated ketal reduction with borane dimenthyl sulphide - Bartels, Birgit (Department of Chemistry, 2016)
Carbonyl reduction to secondary alcohols is a fundamentally important reaction in organic chemistry and many reagents have been developed for achieving this transformation efficiently, with regard to both the optical and material yield. An alternative approach, popularized in recent times, is the dissociative reduction of ketals to afford ethers as protected secondary derivatives and a number of approaches accomplishing a high degree of stereoselectivity have been developed. This thesis describes a study of a novel reagent combination, namely borane dimethyl sulphide and trimethylsilyl trifluoromrthanesulphonate (TMSOTf) for reductive ketal cleavage.